2008
DOI: 10.1103/physrevd.77.113015
|View full text |Cite
|
Sign up to set email alerts
|

Softly brokenμτsymmetry in the minimal seesaw model

Abstract: Neutrino oscillations data indicates that neutrino mixings are consistent with an apparent À exchange symmetry in neutrino mass matrix. We observe that in the minimally extended standard model with the seesaw mechanism, one can impose $ symmetry at the tree level on all Lagrangian terms, but for the mass difference among and leptons. In the absence of any new extra physics, this mass difference becomes the only source for the breaking of such a symmetry, which induces, via quantum corrections, small but predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…This symmetry has been extensively studied [40][41][42][43][44][45][46][47][48][49][50][51][52]. After the measurements of θ 13 , dedicated investigations of the μ-τ exchange symmetry can be found in ref.…”
Section: μ-τ Exchange Symmetrymentioning
confidence: 99%
“…This symmetry has been extensively studied [40][41][42][43][44][45][46][47][48][49][50][51][52]. After the measurements of θ 13 , dedicated investigations of the μ-τ exchange symmetry can be found in ref.…”
Section: μ-τ Exchange Symmetrymentioning
confidence: 99%
“…Nevertheless, having two of the predicted mixing angles so close to the observed values could be a good indication that µ ↔ τ symmetry does have something to do with fixing the observed lepton mixings at some level. As it was shown in a recent analysis [8], the effect of the breaking produced by the sole charged lepton sector on neutrino mixings is rather negligible. This is because in a SM with three right-handed neutrinos, dressed with an effective µ ↔ τ symmetry in all neutrino couplings, the µ and τ mass difference enters into the mixings only through one-loop quantum corrections mediated by the W boson, and thus, it comes out very suppressed.…”
Section: +0016mentioning
confidence: 64%
“…Of course, when CP phases are canceled (taking all masses to be real), the above expressions reduce to the previous results as given in Eqs. (8)(9). Interesting enough, Eq.…”
Section: Cp Phase Contributionmentioning
confidence: 99%
“…3 Some recent studies on the minimal seesaw model can be found in Refs. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%